Cavitation as a stage of necrectomy in the treatment of postpartum endometritis - A. Yu. Khavansky; B. V. Arakelyan; V. A. Linde; M. A. Levkovich; A. A. Gaidarova; Yu. V. Vasiliev (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова)
Introduction. Postpartum endometritis is an inflammation of the endometrium with possible involvement of the myometrium that occurred after childbirth or cesarean section. The main components of its treatment are antibiotic therapy and removal of necrotic contents of the postpartum uterine cavity (necrectomy). Ultrasound cavitation with fluid aspiration was used for necrectomy.The objective of this study was to evaluate the effectiveness of necrectomy using ultrasonic cavitation with aspiration of various fluids in the treatment of postpartum endometritis. furacilin solution.Materials and methods. 45 puerperants with postpartum endometritis were examined and treated. The patients were divided into 3 groups: in the 1st group, treatment was performed without necrectomy; in the 2nd group, cavitation of the uterine cavity using isotonic sodium chloride solution was added to the treatment; in the 3rd group, cavitation of the uterine cavity with furacilin solution.Results. On the 7th day of treatment, all patients noted an improvement in well-being, normalization of temperature parameters, and reduction of uterine soreness. At the same time, the most pronounced uterine involution was observed in patients of the 3rd group. For example, in patients of group 1, the length of the uterus decreased by 16.9 %, and in patients of group 3 – by 29.5 %. The dynamics of the content of tumor necrosis factor α and interleukin 10 in blood serum was also most pronounced in patients of group 3. Thus, in patients of group 1, the content of IL10 decreased by 84.1 %, and in patients of group 3 – by 90.9 %. The bed-day in this group was 9.3 days, and in the 3rd group was 7.0 days.Conclusion. The inclusion of ultrasound cavitation of the uterine cavity with furacilin solution in the treatment of patients with postpartum endometritis increases the effectiveness of treatment of this disease.